Use of an Immunochromatographic Assay for Rapid Detection of Trichomonas vaginalis in Vaginal Specimens - Huppert, Jill S. (American Society for Microbiology, 2005)
Trichomonas vaginalis infection is estimated to be the most widely prevalent nonviral sexually transmitted infection in the world. Wet-mount microscopy is the most common diagnostic method, although it is less sensitive than culture. The OSOM Trichomonas Rapid Test (Genzyme Diagnostics, Cambridge, Mass.) (referred to here as OSOM) is a new point-of-care diagnostic assay for T. vaginalis that uses an immunochromatographic capillary flow (dipstick) assay and provides results in 10 min. The purpose of this study was to determine the test characteristics of OSOM compared to those of a composite reference standard (CRS) comprised of wet-mount microscopy and T. vaginalis culture. This multicenter cross-sectional study enrolled sexually active women ≥18 years of age who presented with symptoms of vaginitis, exposure to T. vaginalis, or multiple sexual partners. Vaginal-swab specimens were obtained for T. vaginalis culture, wet mount, and rapid testing. The prevalence of T. vaginalis in this sample was 23.4% (105 of 449) by the CRS. The sensitivity and specificity of OSOM vaginal-swab specimens were 83.3 and 98.8%, respectively, while wet mount had a sensitivity and specificity of 71.4 and 100%, respectively, compared to the CRS. OSOM performed significantly better than wet mount (P = 0.004) and detected T. vaginalis in samples that required 48 to 72 h of incubation prior to becoming culture positive. The performance of the rapid test was not affected by the presence of coinfections with chlamydia and gonorrhea. The OSOM Trichomonas Rapid Test is a simple, objective test that can be expected to improve the diagnosis of T. vaginalis, especially where microscopy and culture are unavailable.